THE EFFECT OF GCG IMPLEMENTATION AND RISK PROFILE ON FINANCIAL PERFORMANCE AT GO-PUBLIC NATIONAL COMMERCIAL BANKS - Haryati, Sri; Kristijadi, Emanuel (Journal of Indonesian Economy and Business, 2014)
The research tests the effect of the risk profile and the application of corporate governanceon financial performance at go-public national commercial bank. The data were taken fromtheir financial statement and GCG assessment published during 2008-2010, analyzed usingSEM with generalized structured component analysis (GSCA). It shows that risk profile has nosignificant and positive effect on the financial performance. Among the four risk profiles,liquidity risk has the best discriminate validity. However, GCG has significant and positiveeffect on the financial performance, and only financial and non financial transparency has thebest convergent validity. Banks five financial performance indicators have good validity.Beside, ROA, NIM and CAR have good validity in which ROA has the highest loading estimate.Keywords: good corporate governance, risk profile, profitability, capital